Build your community : turn your connections into a powerful online community - Millington, Richard (Pearson Education Limited, 2021)
"Your customers are overwhelmed: they avoid your advertising, ignore your emails, and don't engage with your tweets. Yet, they also expect you to respond to their every need instantly and personably. Build Your Customer Community, explains how you can harness their passion and expertise so you can cut support costs by up to 100%, generate millions of dollars in new business, and double customer spending. The key to thrive in the future is to stop treating customers as a passive audience, and embrace them as an engaged community where you can capture their full potential. Build Your Customer Community is your step-by-step guide to start your community, delight your members, and reap the rewards. You're going to learn why smart businesses have community members telling them exactly what they want to buy, help co-develop their products with them, and use their community as a testbed for marketing ideas before any major campaign. You will learn how to: 1) get customers to solve each other's problems, reduce your support costs, and drastically improve customer satisfaction 2) increase customer spending and reduce churn by building a powerful sense of community among your customers 3) turn your customers into the ultimate sales team who identify leads and help you close sales 4) identify exactly what customers desire and get your customers co-creating the products and services they want to buy 5) become the definitive destination for expertise in your sector by harnessing the full expertise of your customers." -- by publisher.